2023
DOI: 10.1002/cbic.202300637
|View full text |Cite
|
Sign up to set email alerts
|

Cleaving Folded RNA with DNAzyme Agents

Daria D. Nedorezova,
Mikhail V. Dubovichenko,
Arseniy J. Kalnin
et al.

Abstract: Cleavage of biological mRNA by DNAzymes (Dz) has been proposed as a variation of oligonucleotide gene therapy (OGT). The design of Dz‐based OGT agents includes computational prediction of two RNA‐binding arms with low affinity (melting temperatures (Tm) close to the reaction temperature of 37oC) to avoid product inhibition and maintain high specificity. However, RNA cleavage might be limited by the RNA binding step especially if the RNA is folded in secondary structures. This calls for the need of two high‐aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 45 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…This binding step might be a limiting stage for suppression of natural mRNA in vivo . We, therefore, strongly advocate for using long model RNA substrates in optimization of Dz agents, as was expressed by us earlier ( 36 ) and supported recently by Zhang et al. ( 46 ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This binding step might be a limiting stage for suppression of natural mRNA in vivo . We, therefore, strongly advocate for using long model RNA substrates in optimization of Dz agents, as was expressed by us earlier ( 36 ) and supported recently by Zhang et al. ( 46 ).…”
Section: Discussionmentioning
confidence: 57%
“…It was shown earlier that the increase in the affinity of RNA-binding arms in Dz agents increases the cleavage efficiency of folded RNA substrates ( 11–14 ). However, none of the prior studies with one recent exception ( 36 ) have optimized the structures of Dz agents for the cleavage of folded RNA. We reasoned here that a fair comparison of the cleavage efficiency and selectivity of the bivalent agents should be done with optimal rather than suboptimal Dz of the traditional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the parameters with that of Dz of conventional design optimized for the same RNA targets earlier. [17] Folded RNA Can Be Efficiently Cleaved by Long-Armed Dz of Conventional Design if the Cleavage Products are Folded in Stable Secondary Structures RNA-1 had the most stable global and local secondary structures of the three substrates used (Figure 1). Surprisingly, DNM approach did not improve the rate of RNA-1 cleavage.…”
Section: Dnm In the Context Of Dnazyme Technology For Rna Cleavagementioning
confidence: 99%
“…We, therefore, concluded that fragments of biological RNA that produce folded RNA fragments might be considered as promising targets for Dz agents. [17] In this case, however, Dz of conventional designs need to be equipped by long RNA binding arms, which may jeopardize their specificity when exposed to human transcriptome. DNM approach, therefore, may become a strategy to achieve efficient and selective cleavage in such challenging cases.…”
Section: Dnm In the Context Of Dnazyme Technology For Rna Cleavagementioning
confidence: 99%